Characterization of Annexin V Fusion with the Superfolder GFP in Liposomes Binding and Apoptosis Detection - Abbady, Abdul Qader; Twair, Aya; Ali, Bouthaina; Murad, Hossam (Frontiers in Physiology, 2017)
Programed cell death is a critical and unavoidable part of life. One of the most widely used markers for dying cells, by apoptosis or pyroptosis, is the redistribution of phosphatidylserine (PS) from the inner to the outer plasma membrane leaflet. Annexin V protein is a sensitive and specific probe to mark this event because of its high affinity to the exposed PS. Beyond that, annexin V can bind to any PS-containing phospholipid bilayer of almost all tiny forms of membranous vesicles like blood platelets, exosomes or even nanostructured liposomes. In this work, recombinant human annexin V was produced as a fusion with a highly fluorescent superfolder derivative of the green fluorescent protein (sfGFP) in Escherichia coli. The fusion protein(sfGFP-ANXV, 64 kDa), annexin V (ANXV, 40 kDa) and sfGFP (27 kDa) were separately produced after cloning their encoding genes in pRSET plasmid, and all proteins were expressed in a soluble form, then purified in high yields because of their N-terminal 6×His tag ( 150 mg of pure protein per 1 L culture). Superiority of this fluorescent fusion protein over fluorescein-conjugated annexin V was demonstrated in binding to phospholipids (and their liposomes), prepared from natural sources (soya bean and egg yolk) that have different content of PS, by using different methods including ELISA, dot-blotting, surface plasmon resonance and flow cytometry. We also applied fluorescent annexin V in the detection of apoptotic cells by flow cytometry and fluorescent microscopy. Interestingly, sfGFP-ANXV fusion was more sensitive to early apoptotic stressed HeLa cells than fluorescein-conjugated-ANXV. This highly expressed and functional sfGFP-ANXV fusion protein provides a promising ready-to-use molecular tool for quantifying liposomes (or similarly exosomes) and detecting apoptosis in cells.